Correlation between hyposalivation and xerostomia in patients with head and neck cancer - Cella, Hortência Resende dos Santos Della; Dantas, Juliana Borges de Lima; Fortuna, Tila; Santos-Leite, Éder Gerardo dos; Lima, Hayana Ramos; Carrera, Manoela; Martins, Gabriela Botelho (Journal of Oral Diagnosis, 2022)
Introduction: Saliva plays an important role in maintaining oral homeostasis. However, cancer treatment can induce transient or permanent adverse effects on the salivary glands. Objective: This study aimed to evaluate the correlation between xerostomia and salivary flow velocity (SFV) in patients undergoing antineoplastic treatment for head and neck cancer (HNC), under the Public Health System in the city of Salvador-BA. Materials and Methods: This cross-sectional observational study evaluated medical records of patients diagnosed with HNC and treated by the Oncology Service of the High Complexity Unit in Oncology Nossa Senhora de Fátima - Irmã Dulce Social Works - dental team between January 2019 and March 2020. After anamnesis, stimulated saliva was collected at the 1st and 24th radiotherapy sessions to quantify SFV, and a xerostomia questionnaire was administered for assessments based on a visual analogue scale (VAS). Descriptive statistics were performed, and categorical variables are presented as means, percentages, and coefficients of variation. Results: Medical records of 200 patients were assessed and 16 patients were included in the study. The sociodemographic profile showed a predominance of men (62.50%), aged between 46 and 70 years (56.25%), of mixed ethnicity (43.75%), with incomplete primary education (43.75%), alcoholics (56.25%), and non-smokers (56.25%). Tumor and treatment data showed a predominance of exclusive radiotherapy (50%), location in the larynx (31.25%), and T1/T2 staging (56.25%). The mean SFV of patients was 1.75 mL/min and 0.71 mL/min at the 1st and 24th session, respectively, revealing that irradiation reduced SFV. All domains of the xerostomia scale showed an increase in the means obtained, which indicated worsening of xerostomia between the 1st and 24th sessions. Conclusions: An inverse correlation was observed between the mean VAS scores and SFV in patients with HNC. Further studies to correlate hyposalivation (objective sign) with xerostomia (subjective symptoms) are recommended.